Islamic capital market industry in nation development - Abu Bakar, Azizi; Mohamed Elias, Ezanee (2013)
Capital market refers to long-termfinancial market assets consisting of debt instrument involve both government and private sectors that have an expected maturity for more than one year and corporate stocksthat do not have fixed maturities and also the futures commodity.The main important elements of capital markets is the equity capital associated with individual or institutional owner ship over the shares of the company.It also includes capital debts related to business loans and financing for infrastructure development purposely for Asia until year 2000 and it is expecting to reach at least USD1 trillion. Based on record, Malaysia's herself requires an amount of RM550 billion to be successful for the Seventh Malaysia Plan (1996-2000) ago. Thus,this paper will discuss the contribution of the capital market industry towards the development of the economy mainly from the Islamic capital perspectives.The early results indicated that Islamic capital market possessed an optimistic contribution which is equally impressive as conventional capital market in contributing to the development of acountry.